A Proposed Method of Group Observation and Note-Taking from a Psychoanalytical Perspective. (March 2013) - Gimenez, Guy; Pinel, Jean Pierre
Although the taking of notes in clinical group settings is an important issue, it has received surprisingly little attention. Given that it is one of the tools in the analyst's armoury and part of his or her internal framework, it certainly deserves detailed reflection. Taking notes forces us to question our implicit choices of what is (or is not) relevant to pick up, note down and interpret, as well as the way we process the clinical material both during and after sessions. For all these reasons, we believe it is important to make a careful study of our observation method. This article identifies the criteria for relevant note-taking in a group setting and describes a notation method devised specifically for group settings. The aim of this method is to link different levels of psychic reality, all the while keeping them separate. To this end, the notes are divided into four columns: the group associative chain, the underlying 'basic scenarios', internal and intertransferential reactions, and hypotheses about the observed phenomena.